KAJIAN TINGKAT PENERIMAAN KONSUMEN TERHADAP PRODUK TERASI IKAN DENGAN PENAMBAHAN EKSTRAK ROSELA - N Ira Sari; Edison '; Sukirno Mus (Fakultas Perikanan dan Kelautan, Universitas Riau, 2009)
The study was conducted in the Laboratory of Fisheries Technology andFood Chemistry Faculty of Fisheries and Marine Science University of Riau. Theresearch objective was to determine the influence of the addition of rosela extractwith different concentrations of trash fish paste of consumer acceptance. Thebenefits of this research was as material information about the use of roselaextract to be added to process of making trash fish paste so getting a qualityproduct and customer favorite. The method used in this study are experimentingwith methods of experimental design used is Complete Random Design (RAL) afactor with three level, ie without the addition of 0% rosela extract (A0), theaddition of 10% rosela extract (A1) and the addition of 20% rosela extract (A2) tothe weight of the trash fish paste with three replications. The parameter used wasthe organoleptic testing (appearance, texture, aroma and taste) and nutirentanalysis (water content, protein, fat, ash and pH).Based on trash fish paste of the preferences test with the addition of roselaextract real influence on appearance, odor and flavor. Result of the preferencestest was the best treated favorite trash fish paste with the addition of the roselaextract 10% (A1) with a percentage of revenue appearance 72.50% (58 people),the texture of 70.00% (56 people), the odor of 68.25% (55 people) and the flavorof 72.50% (58 people). Characteristic fish paste with the addition of the roselaextract 10% (A1) colour appearance a dark brown, the texture was more denseand compact, distinctive odor rosela and fish paste, distinctive taste fish paste andsour. Test results nutirent analysis that fish paste with the addition of the roselaextract 10% (A1), which is 37.49% water content, protein content, 28.89%, 1.35%fat, 14.47% ash content and pH value of 5, 82.